Теория микрополярных ортотропных упругих слоистых тонких пластин - С. О. Саркисян; А. Ж. Фарманян (National Academy of Sciences of Armenia)
В данной работе на основе обобщённой на микрополярный случай кинематической гипотезы прямой линии для всего пакета пластинки построена общая теория микрополярных ортотропных упругих слоистых тонких пластин.In the present paper general theory of micropolar orthotropic elastic multilayered thin plates is constructed on the basis of generalized for micropolar case kynemathic hypothesis of straight line for the whole package of the plate. Աշխատանքում սալի ողջ փաթեթի համար միկրոպոլյար դեպքի համար ընդհանրացված ուղիղ գծի վարկածի հիման վրա կառուցված է միկրոպոլյար օրթոտրոպ առաձգական շերտավոր բարակ սալի ընդհանուր տեսությունը:
Keywords: Mechanics of deformable solids; Material properties given special treatment; Thin bodies, structures